2022
DOI: 10.1111/tgis.12897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small‐group learning on the assessment of professional skills through a PBL activity

Abstract: Working on a real project emphasizes an active learning environment such as that used in collaborative pedagogy, where students learn to resolve problems and improve their professional skills. Engineering programs are invested in improving learning by focusing on real hands‐on experience. The crisis caused by COVID‐19 will lead to a reduction in the number of enrollments in many university programs. Therefore, it is important to investigate how the dynamics of small groups will affect the active learning proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(48 reference statements)
0
2
0
1
Order By: Relevance
“…Once students have solved a problem, PBL teaching method requires them to present their solution and results to others. This can be done through oral presentations, group discussions, or presentation of manuscripts [13][14]. Through the presentation of results, students can consolidate their learning results, improve their expression skills, and gain further learning and improvement from feedback from other students.…”
Section: Pbl Teaching Methodsmentioning
confidence: 99%
“…Once students have solved a problem, PBL teaching method requires them to present their solution and results to others. This can be done through oral presentations, group discussions, or presentation of manuscripts [13][14]. Through the presentation of results, students can consolidate their learning results, improve their expression skills, and gain further learning and improvement from feedback from other students.…”
Section: Pbl Teaching Methodsmentioning
confidence: 99%
“…However, the literature also shows that many studies develop WebGIS for a purpose not associated with monitoring COVID-19. A total of eight papers developed geotechnologies for educational purposes [44][45][46][47][48][49][50][51]. The literature review also identified geotechnologies for public resource management [52] and tourism [53].…”
Section: International Webgis Applicationsmentioning
confidence: 99%
“…• La implementació d'activitats pràctiques centrades en l'aprenentatge basat en problemes per fomentar la participació, la motivació, la implicació i l'aprenentatge autònom de l'alumnat en una situació en què l'autonomia dels i les estudiants és imprescindible a causa de la situació d'aïllament (Casquero-Modrego et al, 2022;Liu et al, 2022;Pereira et al, 2022).…”
Section: Investigació Recent En L'àmbit D'estudiunclassified